Enhanced hierarchical dynamic bandwidth allocation algorithm with excess bandwidth and SLA techniques for upstream ethernet PON - Sadon S.Kh.; Radzi N.A.M.; Din N.M.; Mustafa I.S.; Al-Mansoori M.H.; Yaacob M. (2023)
Passive Optical Networks (PONs) are thought to be the next step in the development of Access Networks and providing broadband access in the "last mile" area. Ethernet PON (EPON) gains the most attention from the researchers as it offers highly flexible and cost effective solution. In this paper we propose two high level scheduler algorithms inside the Optical Line Terminal (OLT) and Optical Network Units (ONU). In the proposed Dynamic Bandwidth Allocation (DBA) algorithm, the OLT allocates the bandwidth to the ONUs in proportion to the weight associated with the excess bandwidth available, while the ONU preferentially allocates its bandwidth to queues with a strict or non strict priority order. The algorithms provide dynamic bandwidth allocation and separate the burden of queue management fairly between the customer and the network. This led to less complicated and more intelligent equipment has been used on the customer's premises. We show the results of simulations to validate the effectiveness of algorithms presented and to provide quality of service (QoS) for triple play real time services in Ethernet passive optical networks (EPONs). 2009 IEEE.